Successful restoration of failed Achilles tendon surgery with semitendinosus and gracilis tendon graft: a case report - Hung, Yu-Tun; Alizargar, Elaheh; Alizargar, Javad; Hung, Kun-Chin; Chen, Chien-Min; Pan, Ru-Yu (Frontiers in Surgery, 2023)
Objective: This case presentation aims to highlight the challenges and outcomes associated with a partial tear of the Achilles tendon (AT) in an elite marathon runner. The objective was to restore tendon anatomy and optimize strength recovery through surgical intervention.Method: We present the case of a marathon runner who suffered a partial AT tear and underwent an initial surgery that failed. A revision surgery was then performed using a semitendinosus and gracilis tendon graft.Results: The patient underwent surgery 14 weeks after the initial AT injury, but unfortunately experienced a complete AT tear after 6 months. However, the novel aspect of this case is the successful restoration of the failed double-row suture technique through the utilization of a semitendinosus and gracilis tendon graft. Notably, the graft remained intact even under high tendon loading during the 2-year follow-up period.Conclusion: Differential diagnosis should consider partial tears of the AT as a possible diagnosis in the patients with heel pain. Furthermore, it is crucial to prioritize a well-paced post-surgical rehabilitation process in AT surgeries. In cases of failed AT surgery, the utilization of gracilis and semitendinosus tendon grafts can serve as viable options for repairing reruptures.